Penerapan Metode Thariqah Tasalsuli Dalam Meningkatkan Daya Ingat Hafalan Al-Qur’an Santri PPTQ Baitul Abidin Darussalam Wonosobo - Mustofa Hafifi; Nasokah Nasokah; Soffan Rizqi (Journal of Student Research, 2024)
This research aims: 1) To find out the method of memorizing the Al-Qur'an Tariqah Tasalsuli at PPTQ Baitul Abidin Darussalam. 2) To find out the application of the Tariqah Tasalsuli method in improving the memorization of the Al-Qur'an for PPTQ Baitul Abidin Darussalam students. 3) To determine the factors that support and hinder the application of the Tariqah Tasalsuli method in improving the memorization of the Al-Qur'an for PPTQ Baitul Abidin Darussalam students. This research uses a qualitative research approach where the type of research is field. Data collection techniques used participant observation, in-depth interviews and documentation methods. Then data sources were obtained from field research, qualitative research and case studies. The analysis technique used is analysis of data collected by research through methodological tools. The results of the research show that: 1) The Tariqah Tasalsuli method of memorizing the Al-Qur'an at PPTQ Baitul Abidin Darussalam is a suggestion given by Asatidz to students who feel that they still have difficulty memorizing the Al-Qur'an and quickly forget their memorization due to lack of focus and repetition. -repeat the memorization which results in the memorization not sticking in the memory. 2) application of the tasalsuli thariqah method at PPTQ Baitul Abidin Darussalam, starting with the students preparing to memorize the surah by reciting one page over and over then reading it again and again verse by verse while memorizing it when the students have completely memorized the previous verse then they can continue with the second verse, then combined and so until the last verse and even the last surah. Then the students who are ready to submit their memorization come forward to demonstrate their memorization to the teaching ustadz by repeating the previous surah. 3) The most important supporting factor in the Tariqah Tasalsuli Method is the intention and motivation of the students themselves to be able to fluently read and memorize the Koran according to the rules of the science of tajwid. Meanwhile, the most common inhibiting factor is the condition of some students who have never memorized the Koran, so they need to adjust to get used to memorizing the Koran. Another weakness is that students are easily distracted when doing muroja'ah to improve their memorization.